The finnish experiences of high education and alpine skiing - Kuusela, V.-M. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: The purpose of this speech was explain Finnish experiences to combine high education and serious sport training in alpine skiing. Education is very serious part of life to Nordic people and young Finns have gained very good learning results in PISA studies. After completing 9 years of basic education, students can choose between general upper secondary school and vocational upper secondary education. In both school system there is special schools for athletes. Methods and results: These official schools for athletes didn`t serve correctly alpine skiers, because facilities for training were not optimal. 1994 Finnish Ski Federation made decision that training system in Finnish alpine skiing will concentrate in two domestic places; Tahko in Nilsiä and Ruka in Kuusamo. The first training centre was started on august 1994 in Nilsiä and the second in Kuusamo after one year. Ski federation was maybe first sport federations in Finland, who made these kind of radical decision. In both places alpine skier operated with upper secondary school and it was possible to make special program for athletes. Length of program was possible to continue for four years. During the school time athletes could make training 10 hours per week and totally 20 hours if needed. Training was coordinated by full time coaches, who took care of all needs for efficient coaching system. During 10 years Finnish alpine skiers have made breaking through on top level and experience of combining high education and alpine skiing has been success. There is coming more young talented alpine skiers because of good idols on top level. Discussion: The next challenge will be to continue this positive progress to higher education which is provided in two types of institutions: polytechnics and universities. At the moment there is about 12 Sports academies around Finland which have made flexible studying possibilities for athletes. There is lot of problems before this system is working properly; lack of student guidance, flexible studies and university personal, financial aid to students and lack of professional coaches. Finnish Olympic Committee is also concentrated in developing and carrying out funding and support system for young, talented athletes. It support top athletes in combining education and training.